Selection Process by Request - Guzmán Napurí, Christian (2015)
The present article talks us about the procedures for selection by request, explaining how it works as an alternative for the common selection procedure on public procurement.Thus, the author explains the process of selection by request with a public entity, privateentity and an international body.